THE EFFECT OF DAILY PHYSICAL EDUCATION LESSONS ON HUNGARIAN STUDENT’S PHYSICAL ACTIVITY LEVELS AND BODY COMPOSITION - Anna, Protzner; Emese, Trajer; Edit, Bosnyak; Anna, Udvardy; Gabor, Szots; Miklos, Toth; Marta, Szmodis (European Scientific Journal, ESJ, 2015)
Lifestyle, physical activity level and nutritional habits as well as environmental factors are having a greater and greater detrimental effect on the health of various populations. In the present study we systematically researched the physical status of schoolchildren. It is well known that as children grow up, the amount of spontaneous physical activity they perform decreases as they have more mental tasks to do these negative factors can be offset with daily physical education. We measured children participating in physical education on a daily basis, consisting of 5th (10-11 years old) and 9th (14-15 years old) grade students and control groups of 4th (9-10 years old) and 8th (13-14 years old) grade students, respectively, for a total of 196 persons (94 girls and 102 boys). Habitual physical activity was obtained with Actigraph, (GT1M/GT3X) and body fat percentage was calculated from anthropometrical measurements. As expected, we were able to observe a linear correlation between the physical activity levels and the body composition of the participants. The more time the subjects spent performing MVPA (Moderate and Vigorous Physical Activity), the less body fat they had. The recommended MVPA is a minimum of one hour per day, but these Hungarian children had two hours of MPVA per day. Our results lead us to conclude that ninety minutes of additional physical education per week for 7-8 months cannot be considered sufficient for a full impact analysis nor for schoolchildren’s physical activity needs or body composition, though an increase in the amount of time spent in physical education classes shows beneficial effects for these children.